2004
DOI: 10.1051/0004-6361:20040365
|View full text |Cite
|
Sign up to set email alerts
|

The Giant Molecular Cloud associated with RCW 106

Abstract: Abstract.We have mapped the dust continuum emission from the molecular cloud covering a region of 28 pc × 94 pc associated with the well-known H  region RCW 106 at 1.2 mm using SIMBA on SEST. The observations, having an HPBW of 24 (0.4 pc), reveal 95 clumps, of which about 50% have MSX associations and only 20% have IRAS associations. Owing to their higher sensitivity to colder dust and higher angular resolution the present observations identify new emission features and also show that most of the IRAS sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
151
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(169 citation statements)
references
References 37 publications
(61 reference statements)
17
151
1
Order By: Relevance
“…From observations with the VLT MIR VISIR camera, Grave et al (2014) found indications that this region consists of two main luminous sources (O4V and O5V) which account for at least half of the luminosity from this region. As well as being proximate to the Hii region G333.6-0.22, this molecular outflow source is also associated with MSX and 1.2-mm dust sources (Mookerjea et al 2004) and masers of H 2 O and OH (Batchelor et al 1980;Caswell 1998).…”
Section: G333 Outflow/infall Sourcesmentioning
confidence: 87%
See 3 more Smart Citations
“…From observations with the VLT MIR VISIR camera, Grave et al (2014) found indications that this region consists of two main luminous sources (O4V and O5V) which account for at least half of the luminosity from this region. As well as being proximate to the Hii region G333.6-0.22, this molecular outflow source is also associated with MSX and 1.2-mm dust sources (Mookerjea et al 2004) and masers of H 2 O and OH (Batchelor et al 1980;Caswell 1998).…”
Section: G333 Outflow/infall Sourcesmentioning
confidence: 87%
“…Typical outflow masses are 10 to 40 M⊙in each lobe, compared to core masses of order Table 10. IR source fluxes in Jy measured with MSX, IRAS, TIFR balloon-borne telescope (Karnik et al 2001) and SEST/SIMBA (Mookerjea et al 2004). The second row for G333.6-0.2 is for fluxes taken within a 3 ′ aperture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many works, it is assumed that (sub)millimeter clumps/clouds would have a common temperature (e.g., Mookerjea et al 2004;Kirk et al 2006;López et al 2011). This is a logical assumption in the case of isolated clouds, athough it is not valid for regions like Gum 31, where different parts of the nebula are affected by different levels of radiation.…”
Section: Identification Of Dust Clumps At 870 μMmentioning
confidence: 99%